Investigation on Coal Pillar Stability between Different Shapes of Gasifier Cavities under High Temperatures during UCG. (16th February 2022) - Shi, Yue; Yun, Xiaopeng; Zuo, Jianping; Li, Zhengdai; Sun, Yunjiang; Yu, Meilu
Abstract : The shape of the gasifier cavity and the high temperatures induced by underground coal gasification (UCG) have a significant influence on the failure characteristics of the surrounding rock. In this study, the variations in the mechanical properties of the surrounding rock in gasifier cavities subjected to different temperatures (20–700°C) were obtained experimentally, and the results were used to establish numerical models. FLAC 3D was used to analyse the failure of the surrounding rock in drop-shaped and traditional rectangular gasifier cavities. The mechanical parameters of the surrounding rock in the numerical model were assigned a gradient distribution based on the temperature propagation law and the experimental results. The results revealed that the temperature of the surrounding rock has a significant influence on the coal pillar stability, and the surrounding rock primarily undergoes shear failure. As the temperature of the surrounding rock increases, the width of the stable coal pillar increases exponentially; the reasonable widths for coal pillars between adjacent drop-shaped gasifier cavities are 12 m (room temperature), 17 m (700°C and 850°C), 18 m (1000°C), 19 m (1150°C), and 20 m (1300°C). In contrast, the reasonable width of coal pillars in traditional rectangular gasifier cavities is approximately 21 m, which is significantly higher than that for drop-shaped gasifier cavities.